Analisis Faktor-Faktor Yang Berhubungan Dengan Keracunan Merkuri Pada Penambang Emas Tradisional di Desa Jendi Kecamatan Selogiri Kabupaten Wonogiri - Sugeng Rianto; Onny Setiani; Budiyono Budiyono (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2012)
Background : Gold mining at Jendi Village, Selogiri Subdistrict, Wonogiri District is artisanal gold mining without a permit/artisanal mining. The activity of gold mining was carried on traditional methode without a good planning techniques and lack of equipments, which is system of underground mines through making tunel and dweel following quartz vein direction that was predicted have a high gold content. The gold mining at Wonogiri District is divided into some groups which can produce gold in 1-2 grams average per day. Processing system use mix-mercury whereas it can be potentially cause environmental pollution and health problems for communities and workers. The goal of research is to analyse factors which is associated with mercury poisoning of gold mining workers at Jendi Village, Selogiri Subdistrict, Wonogiri District. Methods : This research is was an Explanatory Research with cross sectional approach. Sample was selected using systematic probability sampling. The total of samples were taken 60 workers. The research was taken through laboratory investigation mercury level in blood and interview guide, those were exceed than normal standard by WHO analyzed with Chi Square and Logisttic Regression test. Results: The characteristics of respondents are 17-60 years old, 1 month – 29 years worked periode with 1-18 hours per day. From 60 samples, there were 9 workers using masker, 1 worker using glass eye, 23 workers using boots, 9 workers using long clothes and 27 workers never using self personal protection equipment along doing work. There was found no correlation between periode of work, total of mix mercury used in mining and using personal protective equipments with mercury level in blood. The finding 40 people (66,67%) has mercury poisoning. The most influenced variable to the mercury poisoning is working days in a week and working time in a day of the Traditional Gold Miner at Jendi Village, Selogiri Subdistrict, Wonogiri District. Keywords : Mercury poisoning, Workers, Gold mining